Associations among SPARC mRNA expression in adipose tissue, serum SPARC concentration and metabolic parameters in Korean women. (13th May 2013) - Lee, S.H.; Lee, J.A.; Park, H.S.; Song, Y.S.; Jang, Y.J.; Kim, J.H.; Lee, Y.J.; Heo, Y.
Abstract : Objective: Secreted protein acidic and rich in cysteine (SPARC) is expressed in most tissues and is also secreted by adipocytes. The associations of SPARC mRNA expression in visceral adipose tissue (VAT), subcutaneous abdominal adipose tissue (SAT), serum SPARC concentration, and metabolic parameters in Korean women are investigated. Design and Methods: This is a cross‐sectional study. Fifty‐eight women were recruited, of whom 15 women who underwent bariatric surgery for morbid obesity (BMI mean ± SD: 40.2±5.7 kg/m 2 ), 16 who underwent metabolic surgery for type 2 diabetes (BMI: 28.9±4.5 kg/m 2 ), and, as a control group, 27 who underwent gynecological surgery (BMI: 22.7±2.4 kg/m 2 ). Anthropometric variables, metabolic parameters, SPARC mRNA expression in adipose tissue, and serum SPARC concentration were measured. Results: In all subjects, SPARC mRNA expression was significantly higher in SAT than in VAT. Serum SPARC concentrations (mean ± SE) in morbidly obese subjects, subjects with type 2 diabetes, and normal weight subjects were 267.3±40.2 ng/mL, 130.4±33.0 ng/mL, and 53.1±2.8 ng/mL, respectively. SPARC mRNA in SAT was significantly correlated with BMI, whereas SPARC mRNA in VAT was significantly correlated with BMI and VAT area. Serum SPARC concentration was significantly correlated with BMI, waist circumference, total adipose tissue area, and SAT area. After BMI adjustment, serum SPARC concentration was significantly correlated with fasting insulin concentration and HOMA‐IR score. Multivariate regression analysis showed that BMI and HOMA‐IR were independently associated with serum SPARC concentration. Conclusions: Serum SPARC concentration is significantly correlated with obesity indices and might be influenced by insulin resistance. These findings suggest that SPARC may contribute to the metabolic dysregulation associated with obesity in humans.